Ethnomedical insights into plants used by tribes in the Rif of Al Hoceima and in the Pre-Rif of Taza (two provinces in Northern Morocco) - El Aboui, Fatima Zahra; Lahmass, Mouad; Ghabbour, Issam; Laghmari, Mustapha; Benali, Taoufiq; Khabbach, Abdelmajid; Hammani, Khalil (Ethnobotany Research and Applications, 2025)
Background: Given the richness of Morocco's flora, the diversity of medicinal and aromatic plants, and their contribution to a long medical tradition, a comparative ethnobotanical study was carried out to bio-prospect and preserve their traditional uses. The aim was to identify similarities and differences in practices and beliefs linked to the use of these plants in three different tribes. Methods: An ethnobotanical survey using a pre-established questionnaire was carried out in parallel with the Rif of Al-Hoceima and the Pre-Rif of Taza in two stages. The first stage aimed to record the uses of different medicinal plants by the populations of these two areas, while the second stage was complementary and comparative, focusing solely on the plants cited by one population without the other and verifying their uses by the second population based on samples of these medicinal plants (and/or their real photos). Results: The results obtained allowed us to identify 96 plant species in 51 botanical families, of which Lamiaceae and Asteraceae are the most commonly used. The most commonly treated illness was that of digestive disorders, and the most frequently cited preparation methods were infusion for the pre-Rif and decoction for the Rif. In both provinces, people primarily use the leaf. However, significant distinctions were noted, particularly with regard to vernacular names. We identified 45 plants with different nomenclatures between the Rif and the Pre-Rif. These variations may arise from environmental disparities, distinct cultural traditions, and interactions with other ethnic groups. Conclusions: This comparative ethnobotanical study highlighted both similarities and disparities in the use of medicinal plants between the two provinces. These findings establish a solid foundation for the preservation of traditional knowledge about medicinal plants and suggest promising avenues for future pharmaceutical research and the promotion of sustainable exploitation of plant resources. Keywords: Ethnobotanical survey, Comparative study, Pre-Rif of Taza, Rif of Al-Hoceima - Northern Morocco.